(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This text aims to propose reflections from experimental accounts in the creative processes of artistic light creation, during social distance that have sprung during the Covid-19 pandemic. Its technical and poetical perspectives, mainly about strategies to overcome the difficulties of remote learning during the classes in Bachelors of Scenic Arts degree, intended to enlighten synchronous and digital experiment with light in its conception and establishing a language.